The Pendidikan Kesehatan Gigii pada Anak Usia Sekolah di SDN Kapasa: Dental Health Education in Primary School-Aged Children at SDN Kapasa - Sibualamu, Khalida Ziah; Mustafa, Sri Resky; Saharuddin (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
Background: Dental health problems such as caries are still mostly experienced by elementary school-aged children in Indonesia. Health education is one of the preventive strategies employed to mitigate these problems. Dental health education was chosen as a PkM activity at SDN Kapasa. Objectives: The objective of this activity was to enhance students’ knowledge and attitudes regarding the maintenance of dental health. Methods: The approach used in this activity involved lectures supplemented by audiovisual media. A questionnaire was administered twice, before (pre-test) and after (post-test) the intervention, to assess students' knowledge and attitudes. Data were analyzed using a frequency distribution test. Results: The pre-test results indicated that a majority of students had inadequate knowledge (46.4%) and attitudes (82.1%). In contrast, the post-test results indicated an improvement in knowledge (57.1% rated as good; 42.9% rated as adequate) and attitudes ( 46.4% rated good; 35.7% rated adequate). These findings suggest that dental health education can substantially improve both the knowledge and attitudes of students at SDN Kapasa.